Solusi Islam dalam Pengentasan Kemiskinan menurut Yusuf Qardhawi - Adilla, Muhammad Syiddiqi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The problem of poverty is a very sensitive matter for the wider community because poverty is something that must be reduced in this world. If there are no efforts to reduce poverty for a country, that country will experience setbacks or underdevelopment. Underdevelopment in development, resource development and economic development will run slower than developed countries. When viewed from the poverty rate which is almost rampant in every developed and developing country in all parts of the world. It is because of this problem of poverty that until now has not been resolved for both developed and developing countries, and has become a big thing that must be solved in alleviating poverty. In Islam there are many ways to solve or avoid the poverty line. Indonesia as a developing country with a majority of adherents of Islam must overcome or eradicate poverty in accordance with Islamic Sharia. Thus, Islamic economics is a science that studies human economic behavior which is governed by Islamic religious rules and is based on monotheism as summarized in the pillars of faith and the pillars of Islam. And Yusuf Qardhawi who is the main character or figure of the writer in conceptualizing poverty and solutions in poverty alleviation, namely he argued that there are several basic rules that have been regulated in Islam on economic issues, namely: divinity, ethics, humanity and the middle attitude which is characteristic from Islamic economics.